“Small Has No Inside, Big Has No Outside”: Montreal’s Chinese Diaspora Breaks Out/In Music - Morris, Kim Chow (MUSICultures, 2013)
Through ethnographic fieldwork undertaken from 2003 to 2010, discussion with local musicians, and analysis of concert programs, recordings, live performances, rehearsals, press reviews, musicians’ websites and textual sources, the author examines the means by which the Chinese diasporic community in Montreal negotiates its cultural identity and exerts its agency through musical performance. The author also explores how the tangled relationships of regionally- diverse Chinese immigrants to their birthplaces and their chosen homeland are unravelled, reflecting simultaneous positions as “insiders” and “outsiders.”